Executives Compensation Impact Toward Shareholder Wealth: Company Performance (Empirical Study of Listed Companies in Indonesia Stock Exchange and Categorized as LQ45 Index) - Ananto Prabowo; Devinta Palupi Indah Sari (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
This research aimed to examine the relationship between executives compensation toward shareholder wealth with company performance as a moderating variable. The first is to examine whether executives compensation influences company performance. Secondly, it examines whether executives compensation influences shareholder wealth. Thirdly, it examines whether company performance influences shareholder wealth. Lastly is to examine whether executives compensation influences shareholder wealth with company performance as moderating variable. The populations in this research are using the company that listed in Indonesia Stock Exchange (IDX) and categorized as LQ45 index that falls from 2013-2015. This research uses a purposive sampling method to collect a sample. The sample selected was analyzed using PLS (Partial Least Square) analysis which is an outer model and inner model. The results of this study show that executives compensation does not have a role to determine company performance. The second result shows that executives compensation has positive and influence shareholder wealth significantly. Another result shows that company performance has positive and influence shareholder wealth significantly. The last result shows that company performance is not a moderating variable in the relationship between executives compensation and shareholder wealth. Company performance is an independent variable that has a positive and significant relationship with shareholder wealth